Unbekannte Stridulationsorgane bei Dipteren und ihre Bedeutung für Taxonomie und Phylogenetik der Agromyziden (Diptera: Agromyzidae et Chamaemyiidae). - von Tschirnhaus, Michael (Contributions to Entomology = Beiträge zur Entomologie, 1971)
No genus of agromyzids comprehending more than one species could hitherto be defined by constant features. Now a characteristic complex of stuctures has been discovered in Agromyza and Liriomyza, both genera of many species, which is interpreted as a frictional mechanism because of its parallels to other orders of insects and also on account of noticeable signs of mechanical wear. The structures are extensively described and illustrated, as among the Diptera there is known only one dissimilar frictional mechanism in some Tephritidae.Nomenclatural ActsLemurimyza Spencer, 1965 (Agromyzidae), syn. n. of Phytoliriomyza Hendel, 1931Pteridomyza Nowakowski, 1962 (Agromyzidae), syn. n. of Phytoliriomyza Hendel, 1931ornata (Meigen, 1830) (Cerodontha), comb. n. hitherto Liriomyza ornatahilarella (Zetterstedt, 1848) (Phytoliriomyza), comb. n. hitherto Pteridomyza hilarellamelampyga (Loew, 1869) (Phytoliriomyza), comb. n. hitherto Liriomyza melampyga